2018
DOI: 10.1007/s00231-018-2295-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of aldehyde emissions simulation with FTIR measurements in the exhaust of a spark ignition engine fueled by ethanol

Abstract: This work presents a numerical simulation model for aldehyde formation and exhaust emissions from ethanol-fueled spark ignition engines. The aldehyde simulation model was developed using FORTRAN software, with the input data obtained from the dedicated engine cycle simulation software AVL BOOST. The model calculates formaldehyde and acetaldehyde concentrations from post-flame partial oxidation of methane, ethane and unburned ethanol. The calculated values were compared with experimental data obtained from a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The FTIR technology has proved to be useful in identification and characterization of homopolymers, copolymers, or polymer composite, and it has been successfully applied in the evaluation of polymerization process, characterization of the polymer structure, polymer surface, polymer degradation, and polymer modification [17,19,20]. More common applications of FTIR methodology include: Quality verification of materials; analysis of thin films and coatings [21]; decomposition of polymers and other materials, often through thermogravimetry combined with FTIR [22,23] and mass spectrometry; microanalysis of materials to identify contaminants; monitoring of emissions; and failure analysis [24,25,26]. The speed of FTIR analysis makes it particularly useful in screening applications, while its sensitivity allows many advanced research applications.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR technology has proved to be useful in identification and characterization of homopolymers, copolymers, or polymer composite, and it has been successfully applied in the evaluation of polymerization process, characterization of the polymer structure, polymer surface, polymer degradation, and polymer modification [17,19,20]. More common applications of FTIR methodology include: Quality verification of materials; analysis of thin films and coatings [21]; decomposition of polymers and other materials, often through thermogravimetry combined with FTIR [22,23] and mass spectrometry; microanalysis of materials to identify contaminants; monitoring of emissions; and failure analysis [24,25,26]. The speed of FTIR analysis makes it particularly useful in screening applications, while its sensitivity allows many advanced research applications.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have reported an increase in unregulated emissions (acetaldehyde, formaldehyde, ethanol, ethane, ethene, methane and ammonia) when ethanol was used as a fuel. Zarante and Sodré 12 concluded that acetaldehyde emissions are significant with ethanol fuel owing to the presence of the hydroxyl (OH) group in ethanol. Gaffney and Marley 13 also stated in their study that aldehyde formation during combustion significantly limits the use of alcohol fuels.…”
Section: Introductionmentioning
confidence: 99%